(untitled) (Annual of the Faculty of Philosophy in Skopje, 2023)
In recent years, artificial intelligence has made significant progress, leading to a wide variety of applications, such as speech recognition, product recommendations, language translation, and many other applications. Although gender equality and artificial intelligence can be considered separate fields, they are closely related and mutually influence each other. The purpose of this paper is to outline various aspects of relationship between gender equality and artificial intelligence, to identify interrelationship between them, and to present challenges and possible solutions to problems arising from their connection. This text will present the issue of gender equality in the development of artificial intelligence, but also the impact of artificial intelligence on gender equality; challenges and possible solutions, successful examples and case studies, legislation and policies supporting gender balance in artificial intelligence, the impact of gender equality on quality and innovation in artificial intelligence; the future of dynamics of development of relationship of gender equality and artificial intelligence.